SISTEM INFORMASI E-KANTIN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA DENGAN MENGGUNAKAN FRAMEWORK HTML5 - Kadek Adi Pradana (2020)
The research was conducted to analyze and make an apps based on website that is one of information systems that can be accessed by online for use by the community in campus, there is a process of purchasing food, this is having problems in terms of time and facilities of canteen. Based on it so the system information that made is an apps based on website in aims to simplify the process of transactions and minimize time in the process of delivery. The result of this research is an app based website, in the system is features food delivery and updates of food that conducted by admin. Therefore, the implementation of the website based program needed to support the food delivery transaction in the canteen campus UPN.